CORRELATION FAMILY SUPPORT WITH ANXIETY LEVELS OF PREOPERATIVE PATIENTS DURING THE COVID-19 PANDEMIC IN THE YUDISTIRA ROOM, RSUD - Maftuhah, Lilik; Herin Mawarti; Khotimah, Khotimah (International Journal of Social Science, 2022)
Operations in the midst of the Covid-19 pandemic have an impact, one of which is anxiety. Family support helps patients in dealing with a psychosocial problem that is felt during preoperation, especially to relieve anxiety. The purpose of this study was to determine the relationship between correlation family support with anxiety levels of preoperative patients during the Covid-19 pandemic in the Yudistira room, RSUD Jombang. Correlational research design with cross sectional design. The independent variable is family support, the dependent is the anxiety level of the preoperative patient, the sampling technique used: purposive sampling obtained a sample of 40 respondents, the research instrument used a questionnaire, the Spearman Rho statistic test with a significance level of 0.05. The results showed that most of the family support was in the good category (70%), and the patient's level of anxiety was in the severe anxiety category (50%). Based on the spearman rho statistical test, a significance value (0.000) (p < a) was obtained. Health workers in providing nursing care for preoperative patients are expected to involve the family in handling anxiety in preoperative patients, where the role of the family is very important in handling the anxiety of preoperative patients during the Covid-19 pandemic in the Yudistira Room, Jombang Hospital, so that the surgery will run smoothly.